Tinjauan Yuridis Persyaratan Akreditasi dalam Pengadaan Pegawai Negeri Sipil - Risang Pujiyanto; Netti Iriyanti; Sonny Taufan (Jurnal Hukum IUS QUIA IUSTUM, 2018)
Accreditation  requirements  in  Procurement  of  Civil Servants  in  2017  raise  a  controversy  because according  to  the  Ombudsman  of  the  Republic of  Indonesia these  conditions  are  discriminatory.  This study  examines  the  suitability  of  accreditation  requirements  in  the  Procurement  of  Civil  Servants  in 2017  with  the  applicable  laws  and  regulations.  This  research  is  a  normative  study  using  the  legal approach.  The  results  show  that  the  conditions  for accreditation  are  merely  additional  requirements and  needed  to  guarantee  the  legality  of  the  education  attainment  of  an  applicant.  Accreditation requirements  for  different  general  formation  paths in  each department  have yet  to  be  in accordance with the principle of equality as mentioned in one of the Good Governance General Principles.